A technical review of implemented pulsed electric field generators with different topologies - Krishnaveni Subramani; S. Jeroline Mary (International Journal of Applied Power Engineering (IJAPE), 2026)
Pulsed electric field technology (PEF) seeks application in a variety of industries, such as food processing, wastewater treatment, and biomedical engineering, as it provides a non-thermal substitute for conventional thermal pasteurization techniques. The PEF generators are an increasingly important component of this technology since it necessitates high voltage in the range of 2 kV/cm to 100 kV/cm in food processing to inactivate the microorganisms. Different PEF profiles are required based on different foods and the type of microorganisms present in it. The size of existing PEF producers and space limitations are the major challenges in this technology. Hence, there is a growing need to develop laboratory-scale PEF generators to study and analyze the PEF electrical profile for the specified applications. While the single MOSFET PEF generator is appropriate for high frequency applications, the series linked MOSFET PEF generator, one of the PEFs produced in our lab, is found economical. The voltage boosting concept is used to develop 1.62 kV pulses at 52 kHz from 120 V DC input. This paper majorly studies the circuit topologies, switching strategies, and output performances of PEF generators implemented in the laboratory.